CCR2 Deficiency Impairs Ly6Clo and Ly6Chi Monocyte Responses in Orientia tsutsugamushi Infection - Petermann, Michael; Orfanos, Zacharias; Sellau, Julie; Gharaibeh, Mohammad; Lotter, Hannelore; Fleischer, Bernhard; Keller, Christian (Frontiers in Immunology, 2021)
Orientia (O.) tsutsugamushi, the causative agent of scrub typhus, is a neglected, obligate intracellular bacterium that has a prominent tropism for monocytes and macrophages. Complications often involve the lung, where interstitial pneumonia is a typical finding. The severity of scrub typhus in humans has been linked to altered plasma concentrations of chemokines which are known to act as chemoattractants for myeloid cells. The trafficking and function of monocyte responses is critically regulated by interaction of the CC chemokine ligand 2 (CCL2) and its CC chemokine receptor CCR2. In a self-healing mouse model of intradermal infection with the human-pathogenic Karp strain of O. tsutsugamushi, we investigated the role of CCR2 on bacterial dissemination, development of symptoms, lung histology and monocyte subsets in blood and lungs. CCR2-deficient mice showed a delayed onset of disease and resolution of symptoms, higher concentrations and impaired clearance of bacteria in the lung and the liver, accompanied by a slow infiltration of interstitial macrophages into the lungs. In the blood, we found an induction of circulating monocytes that depended on CCR2, while only a small increase in Ly6Chi monocytes was observed in CCR2-/- mice. In the lung, significantly higher numbers of Ly6Chi and Ly6Clo monocytes were found in the C57BL/6 mice compared to CCR2-/- mice. Both wildtype and CCR2-deficient mice developed an inflammatory milieu as shown by cytokine and inos/arg1 mRNA induction in the lung, but with delayed kinetics in CCR2-deficient mice. Histopathology revealed that infiltration of macrophages to the parenchyma, but not into the peribronchial tissue, depended on CCR2. In sum, our data suggest that in Orientia infection, CCR2 drives blood monocytosis and the influx and activation of Ly6Chi and Ly6Clo monocytes into the lung, thereby accelerating bacterial replication and development of interstitial pulmonary inflammation.